The Correlations between Reward and Elementary School Students’ Learning Motivation - Nurmawati Margolang; Neni Hermita; Zariul Antosa (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2019)
The purpose of this study was to find the correlation between reward and student’s learning motivation. This research is quantitative research. The population in this study is fifth grade students in the seventh cluster of Taman District of Pekanbaru. The sampling technique used by the researchers is the simple random sampling. Researchers took a precision of 10% and the sample used was 115 students. Techniques of collecting data are in the form of questionnaires. Data were analysed using the product moment correlation technique. These results indicate that there is a positive and significant correlation between reward and students learning motivation. The significance value is 0,001 < 0,05. The correlation between reward and students’ motivation is at the low level. The large donations or contributions between reward and student learning motivation is 10,2% from coefficient of determination.